Maximizing temperature sensitivity in a one-dimensional photonic crystal thermal sensor - Manal A. Maher; Arafa H. Aly; Mohamed S. Esmail; S. E.-S. Abd El-Ghany (Scientific Reports)
Abstract This paper focuses on a defective one-dimensional photonic crystal thermal sensor with fabricated layers of gallium nitride, glycerin, and air. The transmission features of this sensor have been presented based on the transfer matrix approach using MATLAB software. Interest in the sensor’s sensitivity to temperature variation is for the sake of the photonic bandgap behavior of the 1D photonic crystal and the thermo-optic effect of glycerin must be preserved over a long time in protecting archaeological artifacts. In this direction, theoretical modeling together with numerical simulation studies are conducted to optimize the refractive index of GaN to enhance sensitivity. This work is going to evaluate the performance of the sensor in terms of the shift in the transmission spectrum of the sensor with the imposition of changes in temperature. The effect of the thickness of the defect layer together with the incident angle on the performance of the sensor will be discussed further. Sensor sensitivities are about 10 nm/°C, with a quality factor reaching a high value of 35,443 at an incident angle of 30°, while sensitivities at an incident angle of 65° have 20 nm/°C and a quality factor of 14,723.